Geographical authentication of virgin olive oil by GC-MS sesquiterpene hydrocarbon fingerprint: Scaling down to the verification of PDO compliance. (September 2022) - Quintanilla-Casas, Beatriz; Torres-Cobos, Berta; Guardiola, Francesc; Romero, Agustí; Tres, Alba; Vichi, Stefania
Abstract: Nowadays, 144 Protected Designations of Origin (PDO) and Protected Geographical Indications (PGI) under the EU quality schemes correspond to extra virgin olive oil (EVOO). As endorsed by the EU Food Fraud Network, PDO/PGI EVOOs are particularly vulnerable to fraudulent practices because of their high economic value. For this reason, the present study aims to develop an instrumental tool to assess the compliance of EVOO with PDO label-declaration using a large sample set (n = 350). As a case study, PDOs from Catalonia were used. Therefore, discriminant analysis based on the sesquiterpene hydrocarbon fingerprint determined by HS-SPME-GC-MS achieved to correctly classify an average of 93.6% of samples among the four Catalan PDOs, leaving unassigned the 6% of the total sampling (external validation results for 3 iterations). On the other hand, the proposed strategy allowed discriminating each Catalan PDO from non-PDO samples produced in different geographical areas with an efficiency between 95% and 99%. Graphical abstract: Image 1 Highlights: SH fingerprint and chemometrics achieved discriminating PDO oils from close regions. Oils from different PDOs using the same cultivars were also discriminated. The same approach allowed verifying the PDO compliance against non-PDO samples. This tool proved to be successful to authenticate olive oils from EU to PDO level.